Metagenomic investigation of viruses in green sea turtles (Chelonia mydas) - Li, Hongwei; Chen, Yuan; Xia, Zhongrong; Zhuang, Daohua; Cong, Feng; Lian, Yue-Xiao (Frontiers in Microbiology, 2025)
Green sea turtles are listed on the International Union for Conservation of Nature’s Red List of Threatened Species. Thus, conservation efforts, including investigation of factors affecting the health of green sea turtles, are critical. Viral communities play vital roles in maintaining animal health. In the present study, shotgun metagenomics was used for the first time to survey viruses in the feces of green sea turtles. Most viral contigs were DNA viruses that mainly belonged to Caudoviricetes, followed by Crassvirales. Additionally, most of the viral contigs were not assigned to any known family or genus, implying a large knowledge gap in the taxonomy of green sea turtle gut viruses. Host prediction showed that most viruses were connected to two phyla: Bacteroidetes and Firmicutes. Furthermore, KEGG enrichment analysis showed that the viral genes were mainly involved in phage-associated and metabolic pathways. Phylogenetic tree reconstruction of Caudovirales terminase large-subunit (TerL) protein showed that most of the sequences were phylogenetically distant. This study expands our understanding of the viral diversity in green sea turtles. In particular, analysis of the virome RNA fraction is exceedingly important for investigating intestinal viromes; therefore, future studies could use metatranscriptomics to study RNA viruses.